Die Videothek: Zur Geschichte und medialen Praxis einer kulturellen Institution - Haupts, Tobias (transcript, 2014)
In the age of the digital film, it seems amazing that the occurrence of its haptic form doesn't date back too far. Tobias Haupt shows how film on video tape emancipated the viewer from the rules of cinema and television, creating not only a new approach to film history, but an entirely new space in the media ensemble in addition to the already established sites of film: the video store. In 1980s Germany, this cultural institution formed a nexus that bundled and tried to answer the new questions of youth protection issues, film distribution, and a different kind of media market.